A clinical study and different modalities of management of ventral hernias - Lavanya, S.; Manvi, P. Naga (International Surgery Journal, 2018)
Background: Ventral hernias are a common problem encountered by the surgeons. Patients developing hernias become restricted from work or usual activities as the hernia enlarges and this demands surgical repair. The objective of this study is to evaluate the predisposing factors, the different modes of presentation, the different methods of surgical repair including the newer methods. Methods: A prospective random study done at Alluri Sita Rama Raju Academy of Medical sciences, Eluru, where in 50 cases of ventral hernias were randomly selected. A thorough case history taken as per the proforma enclosed and relevant investigations were done following which a selective surgical treatment such as anatomical repair and mesh repair were used. Anatomical repair was mainly considered in pediatric and infected cases and the remaining with open and laparoscopic mesh repair. Results: Majority of ventral hernias were seen in the age group of 21 to 60 years with a major female preponderance in umbilical, paraumbilical and incisional hernias, and epigastric hernias common in males. The common predisposing factors identified were previous surgeries, followed by anaemia, multiparity. Majority patients presented with mass or swelling over the abdomen which were reducible. The lower midline incisions were the most common cause for incisional hernias. Most of the patients had a fair preoperative presentation. In this study anatomical and mesh repair (open and laparoscopic) were done. 7 cases lost follow up and no recurrences noted. Conclusions: Among the ventral hernias infraumbilical incisional hernias were common with majority being gyneacological and obstetric procedures. Maximum cases were repaired with Open mesh repair (onlay >inlay) followed by laparoscopic and anatomical repair. With the good knowledge of anatomy, good relaxed anaesthesia and improved surgical skills, the use of synthetic suture and prosthetic material, coverage with antibiotics, post-operative care the outcome of treatment for hernia has improved with insignificant recurrence.